MECHANISMS FOR ENHANCING EFFECTIVENESS IN SCHOOL EDUCATION THROUGH INTERACTIVE TEACHING METHODS - Toyev Bakhtiyor Zarifovich (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2026)
The modernization of contemporary education requires the implementation of innovative pedagogical approaches that actively engage students in the learning process and improve educational outcomes. Interactive teaching methods have emerged as one of the most effective strategies for enhancing the quality and efficiency of school education. Unlike traditional teacher-centered approaches, interactive methods encourage collaboration, communication, critical thinking, problem-solving, and active participation among learners.